Scarification effects on germination of perennial soybean (Nenotonia wightii) - Flores M., Enrique (2020)
The aim of this study was to compare the germination of perennial soybean (Nenotonia wightii) cv. Cooper based on two methods of scarification (hot water and mechanical scarification) versus control treatment (without scarification). Mechanical scarification consisted of scraping the seed with sandpaper (# 125) by hand for 5 minutes. Scarification with hot water consisted of placing the seeds in boiling point water in a 1:3 seed:water ratio for 24 hours. The percentage of germinated seeds was higher in the mechanical scarification treatment with sandpaper (p<0.05) and similar between the treatment with hot water and the control. The highest germination percentage was 37.5, 40, and 96% on days 14, 12, and 9 for the control, hot water, and mechanical scarification treatments, respectively.